2018
DOI: 10.1371/journal.pone.0203046
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of RAGE in inappropriate increase of smooth muscle cells from patients with pulmonary arterial hypertension

Abstract: BackgroundPulmonary vascular remodeling of pulmonary arterial hypertension (PAH) is characterized by an inappropriate increase of vascular cells. The receptor for advanced glycation end products (RAGE) is a type I single-pass transmembrane protein belonging to the immunoglobulin superfamily and is involved in a broad range of hyperproliferative diseases. RAGE is also implicated in the etiology of PAH and is overexpressed in pulmonary artery smooth muscle cells (PASMCs) in patients with PAH. We examined the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…It has only been reported that RAGE and S100A8/A9 are overexpressed in pulmonary artery smooth muscle cells in the absence of any external growth stimulus in patients with either heritable or idiopathic pulmonary arterial hypertension. Nevertheless, further studies are needed to clarify the precise role of S100A8/A9 in the pathophysiology of pulmonary arterial hypertension [205]. Figure 1 illustrates the structure of calcium loaded CLP and summarizes the proposed biological functions.…”
Section: Clp In Pulmonary Embolism and Pulmonary Hypertensionmentioning
confidence: 99%
“…It has only been reported that RAGE and S100A8/A9 are overexpressed in pulmonary artery smooth muscle cells in the absence of any external growth stimulus in patients with either heritable or idiopathic pulmonary arterial hypertension. Nevertheless, further studies are needed to clarify the precise role of S100A8/A9 in the pathophysiology of pulmonary arterial hypertension [205]. Figure 1 illustrates the structure of calcium loaded CLP and summarizes the proposed biological functions.…”
Section: Clp In Pulmonary Embolism and Pulmonary Hypertensionmentioning
confidence: 99%
“…Although RAGE has been defined as a specific marker of AT1 cells, after cell injury [23], RAGE may also be expressed in type 2 alveolar epithelial (AT2) cells [24]. In addition to lung epithelium, RAGE expression has also been noted in many crucial cell types in lung physiology, such as vascular smooth muscle cells [25], airway smooth muscle cells [26], and endothelial cells [27].…”
Section: Inflammation Researchmentioning
confidence: 99%
“…Literature suggests a causative role Our present study also demonstrates that PM-exposed mice had significantly elevated sRAGE in BAL and plasma which is in line with our prior findings that RAGE is pivotal to WTC-PM lung injury 16 . RAGE has been implicated in cardiopulmonary diseases, such as pulmonary arterial hypertension 35 . Further, RAGE is overexpressed in smooth muscle cells of patients with both idiopathic and heritable pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%